Cluster Analysis-Based Discernment of Farmers’ Typologies and Climate Change Adaptation Strategies among Rural Women (Indian Journal of Extension Education, 2025)
Climate change poses significant challenges to agriculture, particularly in vulnerable regions like Uttar Pradesh and Haryana, where women contribute significantly to the agricultural workforce. They play a pivotal role in adopting climate-smart adaptation strategies ensuring food security, economic stability, and environmental sustainability. The study was conducted in 2024 to explore women farmers ‘adaptation strategies using K-means clustering. Based on their prioritization of 16 strategies, randomly selected 100 women farmers were found to belong in four distinct clusters. Cluster 1 emphasized crop and agronomic practices, changing planting dates, crop rotations, and Direct Seeded Rice (DSR). Cluster 2 prioritized mechanization and technology integration, raised-bed planting and laser levelling. Cluster 3 focused on soil and water management and harvesting practices, zero tillage, crop diversification, while Cluster 4 preferred sustainable practices as mulching, Integrated Pest Management (IPM), and bio-fertilizers. The analysis underscores the need for targeted agricultural and extension interventions tailored to each cluster’s unique priorities. Strategies include promoting climate-resilient crops, precision agriculture, conservation techniques, and bio-inputs. Extension approaches such as field demonstrations, custom hiring centers, and capacity-building workshops are recommended. These findings highlight importance of cluster-specific strategies to empower women farmers and enhance their resilience to climate change, contributing to sustainable development goals.